Optimization of MEMS intraocular capacitive pressure sensor - Norliana, Y.; Che Wan Noorakma, A.; Ali, M.; Soin, N.; Hatta, S.F.W.M (2016)
MEMS intraocular capacitive pressure sensor is used for monitoring glaucoma disease. The structure of the diaphragm of MEMS capacitive pressure sensor is one of the important factors which could affect the sensor's performance. In this paper, Taguchi and Two-Level Factorial approach are employed to optimize the size of diaphragm thickness, slot width, and slot length. The typical range of intraocular pressure is at 0 - 60 mmHg and applied on 550 × 550 μm four slotted diaphragms. The effects of sensitivity and linearity on these parameters are investigated. From this study, it is found that the optimized parameters are 4.2μm, 25μm, and 100μm for diaphragm thickness, slot width, and slot length respectively. Simulated results by COMSOL Multiphysics indicate that the optimized parameters produce more sensitivity with high linearity compared to the initial parameters condition.